Biocrust lichen and moss species most suitable for restoration projects. (1st January 2020) - Rosentreter, Roger
Abstract : Reintroducing lichens and mosses to areas slated for restoration or rehabilitation may prove integral to project success by filling the biocrust component (niche) of arid ecosystems. In doing so, it is important to select appropriate species and genetic source material. Some bryophyte and lichen species are early pioneers and are potentially well‐suited for restoration projects. Species traits such as high reproductive rates, rapid establishment rates, and large asexual reproductive propagules can be beneficial for restoration. For instance, the large number of spores produced by some mosses are beneficial for reproductive success in arid environments. In addition to identifying the benefit of reproductive strategies, it is important to take habitat needs into consideration; lichen and moss species that are wide‐ranging both geographically and ecologically are recommended over geographically and edaphically restricted species that occur only in specific habitats, such as calcareous soils. Biocrusts used in specific restoration areas should have similar genetic source material (local provenance), and harsh environmental conditions should be ameliorated.